PEMBATASAN HAK KASASI DAN KONSEKUENSI HUKUM BAGI PENCARI KEADILAN DALAM SISTEM PERADILAN TATA USAHA NEGARA DI INDONESIA - Susilo, Agus Budi (Jurnal Hukum dan Peradilan, 2016)
There were appeal legal effort, cassation and judicial review on Administrative Court. After the Supreme Court Act article 45A paragraph (2) letter c was applied, it was determined that not all administrative settlement dispute can be filled to cassation legal effort. The setting restriction poses legal problems to justice seekers. This article aims to study the solution of cassation rights setting restrictions so that it can be mutual for administrative justice seekers. Based on the analysis that has been done it can be concluded that the regulation on Supreme Court Act article 45A paragraph (2) letter c Act number 5 2014 was not clear in procedures and substantive. Thus the setting restriction in cassation legal effort has to consider the aspect of quality and cases type.Keywords : The restriction of cassation right, Administrative Justice System,justice seeker